Fabrication, characterization, and compressive properties of SLM-fabricated 316L triply periodic minimal surface structures - Hengliang, Fan; Abdullah, Yassin (Institution of Mechanical Engineers, 2026)
Triply periodic minimal surface (TPMS) structures are widely utilized in fields such as aerospace, biomedicine, and sound absorption. This study investigated the fabrication characteristics and compressive properties of 316L stainless steel TPMS structures produced via selective laser melting (SLM). Uniform and gradient Gyroid (G) and I-Wrapped Package (IWP) porous structures with different porosities and unit cell sizes were designed. Specimens were fabricated via SLM and their morphology was evaluated employing scanning electron microscopy (SEM) along with microcomputed tomography (Micro-CT). The Micro-CT and SEM images revealed no defects or broken cells, confirming that SLM can accurately manufacture TPMS porous structures. After fabrication, the actual porosities of uniform porous specimens were 1.62%–5.14% lower than their target values. Both the elastic modulus and yield strength of uniform porous structures decreased progressively with increasing porosity. Although the deformation mode of TPMS structures was unchanged by graded porosity, introducing a porosity gradient significantly increased the compressive strength and energy absorption compared to uniform porosity designs. Using Abaqus software, a finite element model was established to analyze compressive behavior, enabling simulation of the corresponding stress–strain response. The outcomes of the numerical analysis demonstrated strong agreement with the experimental observations. This study systematically compares and validates the uniform porosity and gradient porosity in the 316L TPMS lattice through experiments and finite element analysis. These findings offer guidelines for designing TPMS metamaterials tailored to various operating conditions.